Analysis of Promotion and Creativity in Increasing Family Income of Women Aceh Embroidery Articles in Montasik Sub-District - Filia Hanum; Juwita Juwita (Universitas Serambi Mekkah, 2022)
The purpose of this study was to analyze the influence of promotion and creativity possessed by Acehnese embroidery craftswomen in an effort to market their handicrafts so as to increase family income (a case study on the Acehnese embroidery creative craft business group in Dayah Daboh village, District Montasic). This research belongs to the type of field research with a quantitative approach. The population in this study were women who were members of the Acehnese embroidery craft business group. The sampling method used in this study is non-probability sampling with simple random sampling technique, and data collection techniques using survey methods through questionnaires with a sample of 75 respondents. The method of data processing and analysis uses multiple linear regression with the help of IBM SPSS Statictic 22 which includes classical assumption test and hypothesis testing. The results showed that promotion partially had a positive and significant effect on an increase in income of 0.001 and creativity partially had a positive and significant effect on an increase in income of 0.000. Promotion and creativity variables simultaneously have a positive and significant effect on increasing income by 0.000. Keywords: Promotion, Creativity, and Income